Paparan Debu Kayu Sebagai Faktor Risiko Utama Gangguan Faal Paru di Industri Kayu Lapis - Rachel Octaviari Altruisa; Anita Dewi Prahastuti Sujoso; Ketut Ima Ismara (FORIKES, 2024)
The wood industry is one of the main sources of dust particle pollution that can trigger lung function disorders in workers. Risk factors for lung function disorders include particle size, concentration, and duration of exposure, as well as individual factors such as age and smoking habits. This study aimed to analyze the significance of several risk factors for lung function disorders in workers at PT. Sumber Alam Santoso Pratama, Banyuwangi. This study was a quantitative study with a case-control design, involving 40 respondents as the case group and 40 respondents as the control group. The risk factors measured were age, level of exposure to inhaled wood dust, length of service, use of personal protective equipment, smoking habits and exposure to environmental dust. Data were collected by filling out a questionnaire, then analyzed using a logistic regression test. The results of the analysis showed that the p value for each risk factor was age = 0.328, level of exposure to inhaled wood dust = 0.000, length of service = 0.001, use of personal protective equipment = 0.000, smoking habits = 0.004 and exposure to environmental dust = 0.011. Furthermore, it was concluded that the risk factors for lung function disorders in workers in sequence were the level of exposure to inhaled wood dust, use of personal protective equipment, length of service, smoking habits and exposure to environmental dust.Keywords: lung function disorders; wood dust; wood industry ABSTRAK Industri kayu merupakan salah satu sumber utama polusi partikel debu yang dapat memicu gangguan faal paru pada pekerja. Faktor risiko gangguan faal paru meliputi ukuran partikel, konsentrasi, dan durasi paparan, serta faktor individu seperti usia dan kebiasaan merokok. Penelitian ini bertujuan untuk menganalisis signifikansi beberapa faktor risiko gangguan faal paru pada pekerja di PT. Sumber Alam Santoso Pratama, Banyuwangi. Penelitian ini merupakan studi kuantitatif dengan desain case-control, yang melibatkan 40 responden sebagai kelompok kasus dan 40 responden sebagai kelompok kontrol. Faktor-faktor risiko yang diukur adalah usia, tingkat paparan debu kayu terhirup, masa kerja, penggunaan alat pelindung diri, kebiasaan merokok dan paparan debu lingkungan. Data dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan uji regresi logistik. Hasil analisis menunjukkan bahwa nilai p untuk masing-masing faktor risiko adalah usia = 0,328, tingkat paparan debu kayu terhirup = 0,000, masa kerja = 0,001, penggunaan alat pelindung diri = 0,000, kebiasaan merokok = 0,004 dan paparan debu lingkungan = 0,011. Selanjutnya disimpulkan bahwa faktor risiko gangguan faal paru pada pekerja secara berurutan adalah tingkat paparan debu kayu terhirup, penggunaan alat pelindung diri, masa kerja, kebiasaan merokok dan paparan debu lingkungan.Kata kunci: gangguan faal paru; debu kayu; industri kayu